Divisor Problems Related to Hecke Eigenvalues in Three Dimensions - Jing Huang; Huafeng Liu (Journal of Mathematics)
In this paper, we consider divisor problems related to Hecke eigenvalues in three dimensions. We establish upper bounds and asymptotic formulas for these problems on average.